Pemberian Jus Buah Naga Merah dapat Menurunkan Kolesterol Total Wanita dengan Diabetes Melitus - Ike Ulantari; Kusdalinah Kusdalinah; Eliana Eliana (Jurnal Ilmu dan Teknologi Kesehatan, 2019)
Non-communicable diseases caused global death. Deaths due to non-communicable diseases are expected to continue to increase throughout the world. More than 70% of the global population will die of non-communicable diseases such as cancer, heart disease, stroke and diabetes mellitus. Purpose of this research to analyze effect of red dragon fruit (Hylocereus polyrhizius) on total cholesterol levels of women with type 2 diabetes mellitus. This study was pre-experiment with one group Pretest and Posttest design. The subjects of the study were women with diabetes mellitus who had cholesterol levels of ≥200mg / dl as many as 20 people. The intervention for 14 days was given red dragon fruit juice at a dose of 5.72 g / kgBB. The normality test uses the Shapiro Wilk test. Statistical analysis using the Wilcoxon test. The highest cholesterol level before intervention was 327 mg / dl, lowest was 209 mg / dl. The highest cholesterol level after intervention was 312 mg / dl, lowest was 198 mg / dl. There were differences before and after the intervention (p = 0.025). Red dragon fruit juice supplement can decrease total cholesterol on women with Diabetes melitus.